Chondromyxoid fibroma of patella: a rare case - Ajaya Regmi; Asish Rajak; Sushil Sharma; Chakra Raj Pandey (Journal of Lumbini Medical College, 2020)
Introduction: Chondromyxoid fibroma is a rare benign tumor with aggressive behavior accounting for less than 0.5% of all bone tumors. There are several case-reports of this tumor occurring in different bones. Case report: Here we report a case of 19 years old male with the tumor arising from the inferior pole of right patella which was treated by complete excision of the lesion. The histopathology report was consistent with chondromyxoid fibroma. Conclusion: Chondromyxoid fibroma is a benign but locally aggressive tumor which may occur at unusual sites.